Therapy with Dog Assistant for treatment of anxiety in oncology patients - Lima, Talya Aguiar de; Rodrigues, Sara Martins; Camarço, Maria gabryella pereira da Silva; Jales, Davi Nogueira; Lopes, Lunara de Padua Sousa; Lavor, Lanniel Carvalho Leite de; Aguiar, Sheylla Raquel Diniz Cavalcante; Reis, Renandro de Carvalho (Seven Editora, 2024)
Introduction: Cancer treatment and its side effects can be exhausting and painful. Animal-assisted therapy (AAT) aims to reduce the stress and anxiety caused by cancer treatment. Interaction with the dog helps to increase the production of endorphins and serotonin, which act as a natural analgesic, a mood, sleep and appetite regulator, in addition to reducing cortisol levels, which are related to stress.Objectives: To evaluate the impact of Animal-Assisted Therapy on cancer patients, with an emphasis on mental health, including psychological benefits and adverse effects. Methodology: This is a narrative review on Animal-Assisted Therapy, Mental Health, and Cancer. We use comprehensive descriptors and databases. The inclusion criteria required articles in English or Portuguese, published in full, primary studies and systematic reviews on the relationship between the themes, as well as reports of interventions with animals in cancer patients. Articles in other languages or unrelated articles were excluded. Conclusion: It was concluded that Animal Assisted Therapy is a promising approach in the treatment of cancer, aiming at the emotional well-being of patients. The need for more research and implementation of these complementary practices in healthcare stands out. DOI:https://doi.org/10.56238/sevened2024.001-048